The Effectiveness Of Using “Nas Daily” Youtube Channel In Improving Speaking Skill - Wibowo, Rahmat Ari; Sulistyorini, Dwi (Universitas Ivet, 2023)
The cadets' ability to complete the given language activity and understand the speaking competency constitutes success in speaking English. As a result, the video conference implementation for the Speaking for Formal Interactions course at Ivet University's third-semester cadets in Ship Electrical Engineering has gone off without a hitch. Utilizing different techniques, plans of action, and extra supporting systems like Quizizz, WhatsApp Groups, Zoom Meetings, and others helps with implementation. Speaking professors and cadets also mostly benefit from video conferences in terms of efficacy, ease of connection, technology, and cost rather than experiencing any drawbacks In order to collect the data, a number of approaches, including observation, interviewing, and a questionnaire, were employed to collect the data. The human instrument, observation sheet, questionnaire, and interview guide were study tools at the same time. A technique from Miles and Hubberman (1991) was used to analyze the data that had been gathered. Additionally, the current study used methodological triangulation, which is the use of multiple data-collection techniques, including observation, interview, and questionnaire. In addition to using video conferencing for speaking, the attitudes of the lecturers and the cadets regarding using video conferencing for Speaking for Formal Interactions were also examined. The 15 items in the questionnaire were divided into four categories based on factors including video conferencing efficacy, accessibility, cost, and technology.